Endoscopic Ultrasound‑guided Confirmation of Malignancy Arising from Fistula‑in‑ano - Balekuduru, Avinash Bhat; Bachhav, Gaurav Dinesh; Vishwamitra, Sanjay; Subbaraj, Satyaprakash Bonthala (Journal of Digestive Endoscopy, 2018)
Adenocarcinoma arising from a chronic anorectal fistula (ARF) is rare, and there are no more than 200 cases in literature. We report a case of endoscopic ultrasound‑guided biopsy‑proven adenocarcinoma arising from long‑standing ARF.
Keywords: Adenocarcinoma; anorectal fistula; endoscopic ultrasound